Influence of the morphology and microstructure on the photocatalytic properties of titanium oxide films obtained by sparking anodization in H3PO4 - Sikora, Mariana de Souza; Rosario, Adriane Viana; Pereira, Ernesto Chaves; Paiva-Santos, Carlos O. [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
The aim of this paper is to investigate changes in morphology and microstructure of TiO2 films, prepared by sparking anodization of Ti in a H3PO4 solution, by applying different formation charges. We show that although films obtained by this technique are rarely used in photocatalytic applications, the morphological and microstructural changes during sparking anodization produce TiO2 films that can be used as photocatalysts. In contrast to qualitative analysis commonly found in the literature, we used quantitative methods of analysis to quantify average pore diameter and pore density from the morphology and structural parameters from X-ray diffraction (XRD) patterns using the Rietveld refinement. The results indicated that changes in both the morphology and crystalline structure have a strong influence on the photoactivity of the films. From this investigation, we concluded that, for films prepared in early stages of anodization, the morphology had the biggest influence on photoactivity, and after applying 72C of charge, crystalline properties dominated the photocatalytic characteristics of the films. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Titanium oxide; Galvanostatic anodization; Photocatalysis; Porous films